Use of coronary computed tomographic angiography findings to modify statin and aspirin prescription in patients with acute chest pain - Pursnani, Amit; Celeng, Csilla; Schlett, Christopher L.; Mayrhofer, Thomas; Zakroysky, Pearl; Lee, Hang; Ferencik, Maros; Fleg, Jerome L.; Bamberg, Fabian; Wiviott, Stephen D.; Truong, Quynh A.; Udelson, James E.; et al. (The American journal of cardiology, 2016)
Coronary CT angiography (CCTA) is used in patients with low-intermediate chest pain presenting to the emergency department for its reliability in excluding acute coronary syndrome (ACS). However, its influence on medication modification in this setting is unclear. We sought to determine whether knowledge of CCTA-based coronary artery disease (CAD) was associated with change in statin and aspirin prescription. We used the CCTA arm of the Rule Out Myocardial Infarction using Computed Angiographic Tomography II multicenter, randomized control trial (R-II) and comparison cohort from the observational Rule Out Myocardial Infarction using Computed Angiographic Tomography I cohort (R-I). In R-II, subjects were randomly assigned to CCTA to guide decision making, whereas in R-I patients underwent CCTA with results blinded to caregivers and managed according to standard care. Our final cohort consisted of 277 subjects from R-I and 370 from R-II. ACS rate was similar (6.9% vs 6.2% respectively, p = 0.75). For subjects with CCTA-detected obstructive CAD without ACS, initiation of statin was significantly greater after disclosure of CCTA results (0% in R-I vs 20% in R-II, p = 0.009). Conversely, for subjects without CCTA-detected CAD, aspirin prescription was lower with disclosure of CCTA results (16% in R-I vs 4.8% in R-II, p = 0.001). However, only 68% of subjects in R-II with obstructive CAD were discharged on statin and 65% on aspirin. In conclusion, physician knowledge of CCTA results leads to improved alignment of aspirin and statin with the presence and severity of CAD although still many patients with CCTA-detected CAD are not discharged on aspirin or statin. Our findings suggest opportunity for practice improvement when CCTA is performed in the emergency department.